Aislamiento e identificación de (Metarhizium spp) de tres zonas del subtrópico del Ecuador (Cotopaxi y Pichincha) del cultivo de caña de azúcar (Saccharum officinarum L). - Negrete Sillo, Franklin Estalyn (2023)
The objective of this research was to identify the fungus (Metarhizium spp.) at three subtropical Ecuador zones (Cotopaxi and Pichincha) from sugarcane crop (Saccharum officinarum L), the research methodology was descriptive. Insects and vegetable material were collected using direct collection technique every 9 meters in a zigzag pattern. To obtain native fungi strains, a total of 41 samples were collected, which 17 samples belonged to Palo Quemado locality, 12 samples from El Corazón sector and 12 samples from Pacto locality. The fungi isolation was carried out at Technical University of Cotopaxi, using streaking technique. Forty isolates were obtained from Palo Quemado, locality which 10 isolates were identified as Metarhizium spp., 8 isolates were obtained from adult spittlebug (Mahanarva andigena) and 2 isolates from vegetal material. From El Corazón, locality 20 isolates were obtained, which 9 isolates were identified as Metarhizium spp., 7 isolates were obtained from adult spittlebug (Mahanarva andigena), 2 isolates from vegetal material. From the Pacto sector, 20 isolates were obtained which 10 were identified as Metarhizium spp, 7 isolates obtained from spittlebug (Mahanarva andigena) and 3 isolates from vegetal material. A total of 29 isolates were identified as Metarhizium spp. 22 of the isolates were obtained from spittlebug insects, while 7 isolates were obtained from vegetal material samples.